The Watlington Hoard : coinage, kings and the Viking Great Army in Oxfordshire, AD875-880 - Naylor, John (Archaeopress Archaeology, 2022)
Presenting the complete publication of the objects and coins in the Watlington Hoard, the authors discuss its wider implications for our understanding of hoarding in late 9th-century southern Britain, interactions between the kingdoms of Wessex and Mercia, and the movements of the Viking Great Army after the Battle of Edington in 878.